Financial Inclusion of Women and Gender Gap in Access to Finance: A Systematic Literature Review. Issue 3 (September 2022) - Roy, Priyanka; Patro, Binoti
The consistent gender gap in financial inclusion over time is postulated by World Bank Findex data despite an increase in the overall financial inclusion level around the globe. Women's financial inclusion is significant in line with the promotion of gender equality- one of the 17 Sustainable Development Goals adopted by the United Nations. Academic literatures have fragmented studies on women's financial inclusion and there is a dearth of systematic literature review to comprehend the overall literature landscape in analyzing research gaps. This article is an attempt to conduct a structured systematic literature review to identify factors impacting women's financial inclusion, the associated gender gap and importance of promoting greater financial inclusion for women. Literature reviews are important to map the existing landscape of a study problem and develop further knowledge. This study reviews 75 peer reviewed articles from 2000 to 2021 and presents the findings in a comprehensive manner following a conceptual model. Synthesized evidence reveal the existence of gendered financial inclusion mainly due to demand side factors. Various socio-economic and cultural factors are also seen to influence women's financial exclusion. Based on the mapping of existing findings the study suggests future research directions where emerging themes lie in the areas related to digital finance, financial self-efficacy and financial literacy which are important for enhancing women's financial inclusion.